(untitled) (Research, Society and Development, 2020)
It is known that medicines used during cancer treatment can have harmful effects during pregnancy, both for the mother and the baby. The present paper aims to raise the needs of information on pregnancy prevention and Sexually Transmitted Infections during cancer treatment of adolescents in a large hospital in the central region of state Rio Grande do Sul. This is qualitative approach research, of character descriptive and exploratory, conducted in the period of September and October 2019. Eleven health professionals who worked in the hemato-oncologic sector participated in the study. It was observed in the study that information on sexuality, adolescent pregnancy and Sexually Transmitted Infections practically do not occur because health professionals are focused on cancer treatment of these adolescents. Therefore, it is necessary that the topic be addressed avoiding complications to the health of this teenager, both physical and emotional.